2006
DOI: 10.1262/jrd.18025
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Culture Conditions Using Chemically Defined Media for In Vitro Matured and Intracytoplasmically Inseminated Porcine Oocytes

Abstract: Abstract. The present study investigated in vitro culture methods [droplet and Well of the Well (WOW)] using semi-defined and defined media [modified porcine zygote medium (mPZM)] and the additional effects of insulin on in vitro matured and intracytoplasmically inseminated porcine oocytes. In Experiment 1, in vitro matured and intracytoplasmically inseminated porcine oocytes were cultured for 6 days in the following four groups: 1) mPZM-3 (containing bovine serum albumin) + droplet (30 µl), 2) mPZM-3 + WOW, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
2
16
1
Order By: Relevance
“…This contradiction suggests that sexual maturity of the oocyte donors may not be a dominant factor for production of polyspermic zygotes. In our laboratory, IVP of porcine embryos following ICSI has been applied with success [4,5,9,22,23]. Embryo production by ICSI is the only method capable of completely eliminating the risk of polyspermy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contradiction suggests that sexual maturity of the oocyte donors may not be a dominant factor for production of polyspermic zygotes. In our laboratory, IVP of porcine embryos following ICSI has been applied with success [4,5,9,22,23]. Embryo production by ICSI is the only method capable of completely eliminating the risk of polyspermy.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous reports [4,5,9], pelleted frozen semen was thawed in pre-warmed (39 C) Dulbecco's phosphate buffered saline (PBS; Gibcogen-BRL, Grand Island, NY, USA) containing 0.1% PVA (PBS-PVA) and was washed by centrifugation at 300 × g for 3 min in the same medium.…”
Section: Intracytoplasmic Sperm Injection (Icsi)mentioning
confidence: 99%
See 1 more Smart Citation
“…In Experiment 1, immature oocytes recovered from prepubertal whales (n=4) were cultured for two different IVM culture durations (30 or 40 h) using the WOW method (0.5 mm in diameter) according to previous reports [7,10,11]. After IVM for 30 or 40 h, the nuclear status of the oocytes was determined by whole-mount preparation.…”
Section: Experimental Designmentioning
confidence: 99%
“…These results indicate the importance of adding follicular fluid (FF) collected from pregnant females to IVM medium for whale immature oocytes. It has recently been suggested that chemically defined culture media can be used for IVM and IVC in order to clarify the effectiveness of various additives in the media, such as hormones and growth factors [6][7][8][9]. However, FF has been widely demonstrated to have a positive effect on IVM culture of various mammalian oocytes, and it has been shown that addition of FF during IVM enhances the male pronuclei formation of oocytes after IVF and subseq u e n t e m b r y o n i c d e v e l o p m e n t [ 1 0 - 1 4 ] .…”
mentioning
confidence: 99%